2017
DOI: 10.1002/ijc.31108
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic pathology of early systemic cancer: ERBB2 gene amplification in single disseminated cancer cells determines patient survival in operable esophageal cancer

Abstract: Early metastatic dissemination and evolution of disseminated cancer cells (DCCs) outside the primary tumor is one reason for the failure of adjuvant therapies because it generates molecular genotypes and phenotypes different from primary tumors, which still underlie therapy decisions. Since ERBB2 amplification in esophageal DCCs but not in primary tumor cells predict outcome, we aimed to establish an assay with diagnostic reliability for single DCCs or circulating tumor cells. For this, we evaluated copy numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Equally important, ErbB2 can further improve the ability of tumour cells to migrate and adhere, promote tumour invasion and encourage local and/or distant metastasis 37 . Hoffmann 38 proposed a diagnostic method to detect ErbB2 amplification in single disseminated cancer cells, demonstrating that ErbB2 amplification in esophageal cancer patients is significantly correlated with short-term survival. Previous studies have shown that ESCA can be treated by taking ErbB2 inhibitors such as trastuzumab and ramiximab 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Equally important, ErbB2 can further improve the ability of tumour cells to migrate and adhere, promote tumour invasion and encourage local and/or distant metastasis 37 . Hoffmann 38 proposed a diagnostic method to detect ErbB2 amplification in single disseminated cancer cells, demonstrating that ErbB2 amplification in esophageal cancer patients is significantly correlated with short-term survival. Previous studies have shown that ESCA can be treated by taking ErbB2 inhibitors such as trastuzumab and ramiximab 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells have been known to disseminate into the vascular and lymphatic system, migrating to distant organs and initiating tumor regrowth and recurrence [3]. Clinical evidence has detected CTCs in the blood and DTCs in the bone marrow and lymph nodes; their population is an important indicator for diagnosis, prognosis, and therapeutic response in hepatocellular, breast, brain, and esophageal cancers [1115]. CTC numbers increase following surgery for gastric [4], lung [5], breast [6], hepatocellular [7] and colorectal [8] cancers, and are associated with poor survival.…”
Section: Surgery-induced Cancer Cell Disseminationmentioning
confidence: 99%
“…Some of the upstream regulators can be used as potential diagnostic markers. For example, HNF4A expression can be used as a potential diagnostic tool to discriminate primary gastric cancer from breast cancer metastasis in a Brazilian cohort [46], the ERBB2 gene can be used as a diagnostic marker of early systemic cancer [47], and VCAN is a potential prognostic biomarker for gastric cancer [48]. Some can be used as potential therapeutic targets; for example, NFE2L2 can be used as a therapeutic target for glioblastoma [49], and upregulation of miR-383-5p can suppress proliferation and enhance chemosensitivity in ovarian cancer cells [50].…”
Section: Plos Onementioning
confidence: 99%